Exploring pathways from violence and HIV disclosure without consent to depression, social support, and HIV medication self-efficacy among women living with HIV in Metro Vancouver, Canada. Issue 1 (January 2020) - Deering, Kathleen N; Braschel, Melissa; Logie, Carmen; Ranville, Flo; Krüsi, Andrea; Duff, Putu; Shannon, Kate
We used path analysis to investigate complex pathways from HIV status disclosure without consent, physical/verbal violence and depression, social support, and HIV medication self-efficacy through mediators of HIV stigma among women living with HIV in Canada. In the final model, internalized stigma fully mediated the relationship between physical/verbal violence and reduced medication self-efficacy. Enacted stigma fully mediated the relationship between HIV status disclosure without consent and depression. Internalized stigma (β = 0.252; p < 0.001) had a significant negative direct effect on medication self-efficacy. Enacted stigma had a significant direct effect on depression (β = 0.162; p = 0.037). Findings will help improve services and interventions to promote quality of life and well-being of women living with HIV.